Estudo de seguimento das alterações cardiorrespiratórias e seu impacto na capacidade de exercício físico em pacientes com sobreposição de ICC e DPOC - Santos, Polliana Batista dos (Universidade Federal de São Carlos, 2021)
This thesis consisted of 2 studies that will be described below: The study I, entitled "Left ventricular eccentric hypertrophy, right and left cardiac function in chronic heart failure with or without coexisting COPD: Impact on exercise performance", aimed to evaluate 1) the impact of left ventricular eccentric hypertrophy (LVEH) on exercise performance in patients diagnosed with chronic heart failure (HF) with or without the coexistence of chronic obstructive pulmonary disease (COPD) and 2) the relationship between measures of left and right cardiac function obtained by Doppler echocardiography, clinical features and measures of cardiorespiratory fitness. The study included 46 HF patients with reduced or borderline ejection fraction and LVEH, and of these 23 patients were also diagnosed with COPD, who underwent advanced pulmonary function tests, echocardiography and incremental cardiopulmonary exercise test (CPET) in cycle ergometer. Patients in the HF+COPD group had a lower workload at peak exercise, lower oxygen consumption (VO2), oxygen pulse (PO2), double product (DP), circulatory power (PC) and ventilatory power (PV) when compared to patients diagnosed with HF only. Furthermore, significant correlations were observed between VP and relative wall thickness (r: 0.45 p: 0.03), VE/VCO2 intercept and mitral E/e’ ratio (r: 0.70 p: 0.003) in the HF group. Significant correlations were found between indexed left ventricle mass and RPP (r:−0.47; p: 0.02) and relative VO2 with right ventricle diameter (r:−0.62; p: 0.001) in the HF+COPD group. Our data suggests that combined diagnosis of HF+COPD induced further impairments in cardiorespiratory fitness. Moreover, echocardiographic measures of cardiac function are related to cardiopulmonary exercise performance and therefore appears to be an important therapeutic target when attempting to improve exercise capacity and functional performance of these patients. The study II, entitled "Responses to incremental exercise and the impact of the coexistence of HF and COPD on exercise capacity: a follow-up study" aimed to evaluate: 1) the prevalence of coexistence of HF and COPD in the studied population; 2) the impact of HF+COPD on exercise performance and contrasting exercise responses in patients with only a diagnosis of HF or COPD; and 3) the relationship between clinical characteristics and measures of cardiorespiratory fitness and; 4) verify the occurrence of cardiopulmonary events in the 24-month follow-up period. The study included 124 patients (HF: 46, COPD: 53 and HF+COPD: 25) who initially underwent advanced pulmonary function tests and echocardiography to confirm the diagnosis and stratify the degree of disease severity and subsequently underwent CPET on a cycle ergometer. After performing the CPET, the individuals were followed for a period of 24 months through biannual telephone contacts, where patients or their caregivers answered a questionnaire with questions about the occurrence of exacerbations, hospitalizations, worsening of symptoms or death. Patients in the HF+COPD group demonstrated a lower workrate at peak test (WR), V̇O2, RPP, CP and VP compared to those diagnosed with only HF and COPD. In addition, significant correlations were observed between lean mass and peak V̇O2 (r: 0.56 p< 0.001), lean mass and the oxygen uptake efficiency slope (OUES) (r: 0.42 p<0.001), lean mass and O2 pulse (r: 0.58 p<0.001). The lung diffusion of carbon monoxide (DLCO) was correlated with WR (r: 0.51 p <0.001) and PV (r: 0.40 p: 0.002). Forced expiratory volume in first second (FEV1) is related to V̇O2 (r: 0.52; p <0.001) and WR (r: 0.62; p <0.001). There were no significant differences in the occurrence of cardiopulmonary events and deaths contrasting both groups. The coexistence of HF+COPD induces greater impairment on exercise performance when compared to patients without overlapping diseases, however the overlap of the two diseases did not increase the probability of the occurrence of cardiopulmonary events and deaths when compared to groups with isolated diseases in the period studied. CPET provides important information to guide effective strategies for these patients with the goal of improving exercise performance and functional capacity. Moreover, given our findings related to pulmonary function, body composition and exercise responses, evidenced that the lean mass, FEV1 and DLCO influence important responses to exercise.
Follow-up study of cardiorespiratory changes and their impact on physical exercise capacity in patients with HF and COPD overlap
Keywords: Insuficiência cardíaca; Doença Pulmonar Obstrutiva Crônica (DPOC); Hipertrofia excêntrica; Disfunção ventricular; Teste de exercício cardiopulmonar; Ecocardiografia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL